Divided Attention=Diminished Uptake?Multitasking with Computing Devices at Presentations - Iqbal, Shamsi; Grudin, Jonathan; Horvitz, Eric (Microsoft, 2009)
For colloquium style presentations where audience attention is voluntary, computing devices present an interesting conundrum. Audience members may benefit from simultaneously using a device to take notes or perform other tasks while still attempting to pay attention to the lecture, but the device may also distract its owner, other audience members, or the speaker. We report on two studies of the use of computing devices by people attending colloquium style presentations. We first conducted a survey exploring perceptions of speakers and attendees about the disruptiveness of laptop and smartphone usage during presentations. Then we explored and validated some of the findings in an observational study. We used video to study shifts of attention between devices and presentations, matching them to conceptual blind spots identified by short quizzes given to attendees. We find significant losses of recall associated with increased attention to devices and motivation for attending the presentation, and individual differences in recall of presented information and levels of concern about missing information.